Factors influencing inclination toward agriculture entrepreneurship among students in agriculture learning institute - Abdullah, Farah Adila; Abu Samah, Bahaman (Canadian Center of Science and Education, 2014)
The study has been conducted as a response towards a lack of studies into agriculture entrepreneurship within the local setting. The main attempt of this study is to determine the factors affecting the inclination toward agricultural entrepreneurship among students in agriculture learning institute. This is a quantitative study for which, based on a simple random sampling, a total of 237 students from four agriculture learning institutes were selected as the respondents. The analyzed data has confirmed that the highest mean score was recorded for social value, followed by subjective norm, then behavioral attitude, then closer valuation and finally perceived behavioral control. Based on the data obtained, it is recommended that more studies to be conducted to examine the influencing factors and the challenges faced by the new generations in Malaysia around agriculture entrepreneurship.